2021
DOI: 10.1177/0363546521990801
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Residual Laxity After Anterior Cruciate Ligament Reconstruction on Long-term Laxity, Graft Failure, Return to Sports, and Subjective Outcome at 25 Years

Abstract: Background: In spite of supposedly successful surgery, slight residual knee laxity may be found at follow-up evaluations after anterior cruciate ligament reconstruction (ACLR), and its clinical effect is undetermined. Purpose: To investigate whether a 3- to 5-mm increase in anterior translation 6 months after ACLR affects the risk of graft failure, rate of return to sports, and long-term outcome. Study Design: Cohort study; Level of evidence, 2. Methods: From a cohort of 234 soccer, team handball, and basketba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 52 publications
1
26
0
1
Order By: Relevance
“…Vignos et al 6 reported that tunnel placement during ACLR surgery has an effect on postoperative knee laxity and clinical outcomes. Lindanger et al, 2 while they reported that most of the patients included in their study were treated with the mini-open method and other patients with the transtibial method, did not provide information about the landmarks used for tunnel placements during the ACLR. We believe that these limitations, which were not reported by the authors, should be taken into account when evaluating this magnificent study, which is one of the longest follow-up ACL studies in the literature.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Vignos et al 6 reported that tunnel placement during ACLR surgery has an effect on postoperative knee laxity and clinical outcomes. Lindanger et al, 2 while they reported that most of the patients included in their study were treated with the mini-open method and other patients with the transtibial method, did not provide information about the landmarks used for tunnel placements during the ACLR. We believe that these limitations, which were not reported by the authors, should be taken into account when evaluating this magnificent study, which is one of the longest follow-up ACL studies in the literature.…”
mentioning
confidence: 97%
“…The tibial tunnel was positioned anteriorly and medially, whereas the femoral tunnel was in a posterior and proximal position on the femur condyle. 2 The transtibial tunnel placement technique resulted in a more proximal and posterior tunnel position in the femoral notch, as the offset aimer used the back wall of the epicondyle as a reference, and the femoral tunnel position was predefined by the tibial tunnel placement. 6,7,12 Because the tibial tunnel was more anterior, there was an increased risk of graft impingement, and a moderate notch plasty was therefore performed in all cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Knee laxity after anterior cruciate ligament (ACL) reconstruction (ACLR) is one of the causes of failure, 25 as well as worsening functional outcomes 4 and reduced patient satisfaction, 20 and is considered to lead to the development of osteoarthritis. 14 The factors associated with postoperative knee laxity, excluding surgical technique, include bony morphology, 5 the anterolateral complex 27 and iliotibial band, 19 and lateral meniscal (LM) injuries.…”
mentioning
confidence: 99%
“…We appreciate the interest in our recent paper ''Effect of Early Residual Laxity After Anterior Cruciate Ligament Reconstruction on Long-term Laxity, Graft Failure, Return to Sports, and Subjective Outcome at 25 Years'' 10 and the chance we are given to respond to questions raised by O ¨zbek and Binnet.…”
mentioning
confidence: 99%